A Safety and Coping Planning Intervention for Suicidal Adolescents in Acute Psychiatric Care. Issue 1 (February 2021) - McManama O'Brien, Kimberly H.; Almeida, Joanna; View, Lauren; Schofield, Molly; Hall, William; Aguinaldo, Laika; Ryan, Colleen A.; Maneta, Eleni
Abstract: Transitioning from an acute psychiatric care setting to a less restrictive environment after a suicidal event is arguably the most critical period of suicide risk for adolescents, making comprehensive safety and coping plans for this population ever more critical. In this paper we provide theoretical and empirical rationale for the need for developmental adaptations to current safety planning procedures for suicidal adolescents, as well as the standardization of pediatric safety plans for broader use across settings that provide acute psychiatric care to adolescents. We describe how we developed the Adolescent Safety and Coping Plan (ASCP) using qualitative in-depth interviews with 20 adolescents and their parents, explain the specific components of the ASCP, and give a case example of the ASCP being used with a young adolescent and her parents. Finally, we conclude with a discussion of the barriers and facilitators of the use of the ASCP in settings that provide acute psychiatric care, as well as the need for future research to test the ASCP with diverse adolescent and family populations and settings.